Effects of 17α‐methyltestosterone on the growth performance, development, and reproduction of gynogenetic topmouth culter (Culter alburnus Basilewsky). (27th October 2018) - Chi, Meili; Jia, Yongyi; Cheng, Shun; Liu, Shili; Jiang, Wenping; Zheng, Jianbo; Gu, Zhimin
Summary: This study investigated the effects of 17α‐methyltestosterone (17α‐MT) on the physiological properties of gynogenetic topmouth culter ( Culter alburnus ). Five 17α‐MT concentration (0, 10, 25, 40, and 60 μg/g) groups were set up in Experiment 1, and three treatment and recovery methods of the above five concentrations were studied in Experiment 2. In Experiment 3, fish were fed with increasing concentrations of 17α‐MT (from 40 μg/g to 140 μg/g) in an outdoor pond. In Experiment 1, growth was promoted during the initial 60 days in the 10 μg/g group, whereas inhibition was first observed at 20 days after treatment in the 60 μg/g group. Increased concentration (40–60 μg/g) of 17α‐MT significantly inhibited the expression of FOXL2 and CYP19a gene but significantly activated the expression of AMH and DMRT1 gene. The levels of superoxide dismutase, estradiol, testosterone, growth hormone, and tetraiodothyronine in the 40 and 60 μg/g groups were significantly higher than those in the other concentration groups at 40 days after treatment. In Experiment 2, almost all indexes detected besides the expression of reproduction‐related genes in the 17α‐MT treatment groups were recovered to those in the control groups. All gonads observed in Experiments 1 and 2 remained in a primordial state after treatment with different concentrations of 17α‐MT. In Experiment 3, 100% of the detected gonads developed into testes at 126 and 460 days post‐fertilization after three‐month outdoor 17α‐MT induction. These results suggest that 17α‐MT affects the physiological processes related to sexual differentiation in topmouth culter and that feeding 17α‐MT with increasing dose in an outdoor pond provides an effective protocol for producing neo‐male topmouth culter.